Analysis of the Relationship between Nutritional Behavior in Emergency Conditions and the Nutritional Status of Toddlers: The Case of the Semeru Eruption in Lumajang Regency - Hilda Carmitha Panjaitan; Sumardiyono; Sapja Anantanyu (Jurnal Penelitian Pendidikan IPA, 2023)
Toddlers are a group that is classified as vulnerable in disaster emergencies. One of the areas running a nutrition emergency program is Lumajang Regency, which also has a prevalence of severely wasted reaching 6.9%. A factor that indirectly influences the nutritional status of toddlers is the mother's nutritional fulfillment behavior. This can apply especially in disaster situations that cause local food limitations. This study aimed to analyze the relationship between nutritional behavior in emergency conditions and the nutritional status of toddlers. This research is a cross-sectional study with a quantitative approach. Data collection was carried out by filling out questionnaires for 44 parents of toddlers and measuring the nutritional status of 44 toddlers. Data analysis was carried out by giving a score on the questionnaire and calculating the z-score on the anthropometric data. The Sommers'd test was carried out to analyze the relationship between nutritional behavior and nutritional status. This research found there was no relationship between the mother’s nutritional behavior (including participation, reactions, knowledge, attitudes, skills, and behavior) and the nutritional status of toddlers (p>0.05). This can be caused by food availability factors which directly influence the nutritional status of toddlers.